Interaction of Pseudomonas aeruginosa alkaline protease and elastase with human polymorphonuclear leukocytes in vitro. - Kharazmi, A (1984)
Little is known about the interaction of Pseudomonas aeruginosa extracellular products and human polymorphonuclear leukocytes. The present study was designed to examine the effect of alkaline protease and elastase purified from P. aeruginosa on human neutrophil function. Neutrophil chemotaxis, oxygen consumption, glucose oxidation, superoxide production, and nitro blue tetrazolium reduction were studied. It was found that alkaline protease and elastase at fairly low concentrations (0.05 and 0.0025 micrograms/ml, respectively) inhibited chemotaxis. The inhibitory effect of both enzymes was increased at higher concentrations. The chemotaxis of preincubated and washed cells was also inhibited. Alkaline protease but not elastase inhibited opsonized zymosan-stimulated neutrophil oxygen consumption, whereas neither of the enzymes had any effect on glucose oxidation and nitro blue tetrazolium-reducing activity of stimulated neutrophils. The data on superoxide production ability of the cells indicated that the cells preincubated with enzyme and washed were capable of producing superoxide equal to the amount produced by untreated cells when they were stimulated with phorbol myristate acetate or zymosan. However, when elastase was present in the reaction mixture, the reduction of cytochrome c as a measure of superoxide production was inhibited. Inhibition of neutrophil function, particularly chemotaxis, will have important bearing on the escape of the microorganism from the phagocytic defense system of the host. The role of these products in localized infections and avascular areas such as skin burns, cornea, and, at least initially, in chronic lung colonization in cystic fibrosis patients becomes important.